Impact of sustainable packaging on consumer buying behaviour: a study based on UTAR student - Loh, Yan Min (2024)
The research investigates the factors influencing university students’ buying behaviour toward sustainable packaging in Malaysia, emphasizing four key independent variables: awareness of sustainable packaging, perceived environmental impact, sustainable packaging with smart function and cost perception. Grounded in the Theory of Planned Behaviour, the study examines how these factors interact to shape consumer behaviour. A quantitative research approach was employed, collecting data through surveys from 202 university students. Multiple regression analysis and Pearson correlation were utilized as statistical tools to identify relationships and derive meaningful insights.